Roundabout Arm Capacity Determined by Microsimulation and Discrete Functions Technique - Tollazzi, Tomaž; Šrami, Matjaž; Lerher, Tone (Promet - Traffic&Transportation, 2008)
The paper demonstrates the influence of the multi-channelpedestrian flow on the actual capacity of a one-lane roundabout,using micro-simulation and discrete functions. The proposedmodel is based on the theory of the expected time gap betweenthe units of pedestrian traffic flow, which have the prioritywhen crossing the arm of the roundabout. The proposedmodel represents an upgrade of the previous research in thefield of modelling traffic flows in the one-lane roundabout.Apart from the multi-channel pedestrian flow the disturbancescaused by the circular traffic flow of motorised vehicles at theroundabout are also considered. In this way the model canbetter illustrate the real conditions in traffic. A simulation analysishas been performed on the roundabout arm at KoroskaStreet in Maribor. The results of the analysis have indicated arelatively high reserve of the actual throughput capacity for themain motorized traffic flow in the analysed roundabout arm.The presented model represents a practicable and adaptabletool for planning the roundabout capacity in practice and forthe sensitivity analysis of individual variables on the throughputcapacity of the roundabout.